Combining ability analysis for grain yield and its attributes in Rice (Oryza sativa L.) - Mallikarjuna, BP; Shivakumar, N; Devendrappa, J; Sheela, VD; Bharamappa, G; Halikatti, Ganesh (SAARC Journal of Agriculture, 2014)
Combining ability on grain yield and its components from line × tester analysis of thirty rice hybrids (Oryza sativa L.) produced by crossing three newly developed CMS lines and ten testers of local origin were studied. The analysis revealed higher SCA variance than GCA variance for all the characters except plant height indicating the prevalence of non-additive gene action. The line KCMS 45A and testers MSN 36 and KMR 3 were the good general combiners for yield and its major contributing characters. MSN 99 was the only good general combiner among the male parents for earliness and dwarfness. The hybrids KCMS 46A × MSN 75, KCMS 44A × KMR 4 and KCMS 45A × KMR 3 were identified as potential hybrids for yield contributing characters based on SCA effects which could be exploited in future rice breeding programme by adopting heterosis breeding strategy. The contribution of testers towards the total variance was found higher than lines and line x tester interaction suggesting predominant of testers influence for these characters. DOI: http://dx.doi.org/10.3329/sja.v12i1.21107 SAARC J. Agri., 12(1): 1-8 (2014)